Sosialisasi Gerakan Nasional Revolusi Mental 2022: Budayakan Lingkungan Hidup Hijau, Bersih, dan Sehat di SMAN 10 Bekasi - Ibrahim Nurrasyid Akbar Ibrahim; Adi Susilo Jahja; Markonah Markonah; Ignatius Septo Pramesworo; Tri S. Mildawani; Hikmah A. R.; Widiastuti Murtiningrum; Ch. Endah Winarti; Sri Wahyuni; Suharyanto; Pipin Nuraeni; Belinda Gabriela Sihombing (Perbanas Institute, 2022)
Global climate change has affected human life. Since the industrial revolution, the earth is experiencing global warming that melting the ice in the north pole, caused flooding in everywhere, and making the air temperature more extreme. Facing this problem, world leaders agreed to reduce the negative impact of environmental damage by implementing the idea of SDGs (sustainable development goals). Basically, the SDGs are based on the 3 P (people, planet and profit) concept. The Government of the Republic of Indonesia is committed to implementing the SDGs principles in development. These principles are also in line with the National Movement for Mental Revolution (GNRM) which was launched by the Government. Perbanas Institute is one of 35 universities that passed the selection as recipients of the GNRM Program Self-Management Fund in order to perform the program in educating for clean and green life style. This paper describes the implementation of the program.